1993
DOI: 10.1002/art.1780361019
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of subchondral plate and trabecular bone in cruciate‐deficient dogs with osteoarthritis followed up for 54 months

Abstract: Objective. To evaluate the sequence of changes in articular cartilage, trabecular bone, and subchondral plate in dogs with osteoarthritis (OA), 3 months, 18 months, and 54 months after anterior cruciate ligament transection (ACLT).Methods. Specimens of the medial tibial plateau Submitted for publication May 5 , 1992; accepted in revised form February 9, 1993. were analyzed with microscopic computed tomography (micro-CT) at a resolution of 60 pm, and biochemical and morphologic changes in the femoral articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
150
4
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(186 citation statements)
references
References 18 publications
25
150
4
7
Order By: Relevance
“…In the guinea pig, Layton et al (218) observed that an initial loss of trabecular bone volume fraction, and thinning of trabeculae in early OA was followed by an increase of trabecular bone volume fraction and trabecular thickening in the advanced stages of OA. In a canine ACL transection model of OA, Dedrick et al (220) demonstrated an increase in subchondral bone thickness, accompanied by a decrease in trabecular thickness. Using magnification radiographs in humans, Lynch et al (205) observed an increase in the horizontal trabecular thickness of the tibia in early OA, followed by an increase in vertical connectivity of trabeculae in advanced OA.…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
See 1 more Smart Citation
“…In the guinea pig, Layton et al (218) observed that an initial loss of trabecular bone volume fraction, and thinning of trabeculae in early OA was followed by an increase of trabecular bone volume fraction and trabecular thickening in the advanced stages of OA. In a canine ACL transection model of OA, Dedrick et al (220) demonstrated an increase in subchondral bone thickness, accompanied by a decrease in trabecular thickness. Using magnification radiographs in humans, Lynch et al (205) observed an increase in the horizontal trabecular thickness of the tibia in early OA, followed by an increase in vertical connectivity of trabeculae in advanced OA.…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
“…Based on mCT findings in experimental models of OA, it has been suggested that changes in articular cartilage that occur in OA are associated with changes in the adjoining subchondral and trabecular bone (218)(219)(220). In the guinea pig, Layton et al (218) observed that an initial loss of trabecular bone volume fraction, and thinning of trabeculae in early OA was followed by an increase of trabecular bone volume fraction and trabecular thickening in the advanced stages of OA.…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
“…When cartilage loss started, the subchondral plate and trabeculae underneath cartilage were thin; only later in OA development did the radiographic equivalent of "eburnation" occur with thickening of both areas of bone. These experiments were later replicated in dogs (10). While studies of humans with OA usually focus on those with later-stage disease, at a time when cortical thickening would be expected (11,12), one study of knees from those with fissuring of cartilage but no denudation showed the cartilage bone plug to be less stiff than in unaffected knees of age-matched subjects (13).…”
Section: Does Bony Sclerosis Precede Cartilage Loss In Oa?mentioning
confidence: 99%
“…In established OA, studies of bone of existing noninvasive (in vivo) analytic methods of subchondral bone changes is low, and small changes are difficult to quantify. (8) Several studies in the rabbit and canine anterior cruciate ligament transaction (ACLT) model of OA (9) showed a decrease of trabecular bone volume (10)(11)(12)(13) and a thinning of the subchondral plate (13)(14)(15) early in the disease process. These changes are in contrast to those found in human end-stage OA.…”
Section: Introductionmentioning
confidence: 99%